2016
DOI: 10.1103/physrevb.93.075107
|View full text |Cite
|
Sign up to set email alerts
|

Efficient density matrix renormalization group algorithm to study Y junctions with integer and half-integer spin

Abstract: An efficient density matrix renormalization group (DMRG) algorithm is presented and applied to Y-junctions, systems with three arms of n sites that meet at a central site. The accuracy is comparable to DMRG of chains. As in chains, new sites are always bonded to the most recently added sites and the superblock Hamiltonian contains only new or once renormalized operators. Junctions of up to N = 3n + 1 ≈ 500 sites are studied with antiferromagnetic (AF) Heisenberg exchange J between nearest-neighbor spins S or e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 43 publications
3
10
0
Order By: Relevance
“…61,62 For accurate calculations we have used the modified DMRG algorithm especially designed for Y junction, which renders the accuracy of these calculations comparable to that for linear 1D chains. 52 To maintain a reliable accuracy in the calculations, eigenvectors corresponding to up to 200 largest eigenvalues are retained in each DMRG sweep. The truncation error of the density matrix eigenvalues is less than 10 −12 .…”
Section: Model and Numerical Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…61,62 For accurate calculations we have used the modified DMRG algorithm especially designed for Y junction, which renders the accuracy of these calculations comparable to that for linear 1D chains. 52 To maintain a reliable accuracy in the calculations, eigenvectors corresponding to up to 200 largest eigenvalues are retained in each DMRG sweep. The truncation error of the density matrix eigenvalues is less than 10 −12 .…”
Section: Model and Numerical Techniquesmentioning
confidence: 99%
“…18,21,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] The ground state properties of Y junctions have also been explored using density matrix renormalization group (DMRG) techniques. [51][52][53] A study of TDOS using bosonization technique for spinless fermion was reported by Agarwal et al in Ref. [18] and a collection of FPs (stable for g > 1) were identified which showed enhancement of TDOS in the zero energy limit and the effect was attributed to an Andreev-like reflection off the junction.…”
Section: Introductionmentioning
confidence: 99%
“…18 Y junctions of N = 3n + 1 spins have three arms of n spins plus a central site for which we recently presented an efficient DMRG algorithm. Fig.…”
Section: Dmrg Algorithmsmentioning
confidence: 99%
“…2 of Ref. 18 shows the growth of the infinite DMRG algorithm. A chain of N = 2n + 1 spins can be viewed as two arms of n spins plus a central site.…”
Section: Dmrg Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation